The Influence of Personas' Gender in Design - Vogel, Carl; Ribeiro Lopes, Milena (My University, 2021)
In mobile application design, the construction of personas is a well-known technique that helps designers to empathise with users and to understand their needs. However, there are several issues that lead to stereotyped personas and men’s needs being prioritised in design projects. The under-representation of women in design teams, insufficient user research, the assumption that the default user is a man, and the influence of personal beliefs in the decision making process all obstruct the inclusion of women’s needs in the design process. Therefore, we propose the creation of gender-neutral personas that merge both the needs of men and women using two different approaches, and we compare them with traditional gendered personas. The results of the study confirm our hypothesis — the gender-neutral personas culminated in more gender-inclusive design requirements.
CHItaly 2021: 14th Biannual Conference of the Italian SIGCHI Chapter
PUBLISHED
Keywords: Gender-neutral persona; Gender-inclusive design; Mobile app development; Creative Technologies; Digital Engagement; Digital Humanities; Computational Linguistics; Computational linguistics; Digital Humanities; GENDER; Gender role attitudes; Gender role attitudes & behaviour; computational linguistics; gender bias; Gender